What changes? What remains? The evolution of the street networks in old Beijing city over one century. Issue 2 (3rd July 2018) - Wang, Fang; Jiang, Chunyan; Li, Wei; Li, Jianing; Zhu, Xiaohua
ABSTRACT: The street networks and the urban morphology are assumed to mutually influence each other. Via space syntax, this paper focuses on structural features and evolutionary guidelines of the street network in old Beijing city to examine what changes and what remains. The conclusions are as follows: (1) the deep-layer topological relationship of the street network can also clearly reveal the corresponding political, economic and cultural characteristics; (2) old Beijing city developed its grid-like street network over the past several centuries, which shows a good flexibility and continuity, but also with a long period of traffic pressure in history.